Tinjauan Hukum Pengesahan Perkawinan Melalui Isbat Nikah : (Studi Di Pengadilan Agama Dompu) - Siti Khatija Hafsari; Sahruddin Sahruddin; Musakir Salat (Fakultas Hukum Universitas Mataram, 2023)
This research aims to find out the factors causing unregistered marriages, the procedure for validating Isbat Nikah, and the basis for the judge's consideration in validating Isbat Nikah at the Dompu Religious Court. This research is an empirical study and data analysis used is a qualitative descriptive technique. the factors causing unregistered marriages are the difficulty of polygamy rules, unwed pregnancy and the low level of public education The procedures for validating Isbat Nikah at the Dompu Religious Court are as follows: submit an application, receive a case, examine the case in court, conclusions, and determine the judge with the judge's consideration in the application for Isbat Nikah referring to Compilation of Islamic Law Article 7 and Marriage Law Number 1 of 1974.